امام جلال الدین السیوطی رحمہ اللہ کی زندگی اورعلم تصوف میں خدمات: The Life of Maulana Jala Ud Din Al.Soyothi in the Light of Mysticism (Khairulummah, 2021)
The Almighty Allah has sent many intellectual and pious people after the Last Prophet and Messenger Allah Subhan-o-Tala for the security of Den-e-Islam. They not noly Protect Deen-e-Islam from the foreign imovation but take their roles in its world over spreading. One among these prestigious personalities and intellectual is Jalal Ud Din Asoyothi (849-911). He was a multi sided personality. At the same time he was a great scholar, Author, Reviewer and genius intellectual among his friends. You are the author of approximately 700 books. He has touched my aspect of life in written works. While having such a busy and prestigious life of honesty, truthfulness, rejecting the materialistic life having a heart for the spiritual life. He started to leads the life of mysticism and till death did not leave the life of mystics persons. In this mystic’s life he has written and review many books. Due to this mysticism he was serves the humanity and protect Deen-e-Islam from the false beliefs. In this research paper some of the aspect of mysticism in the light of his research works has been discussed.